Teleworking in United Arab Emirates (UAE): An empirical study of influencing factors, facilitators, and inhibitors - Mohamed G. Aboelmaged; Abdallah M. Elamin (International Journal of Business Science & Applied Management (IJBSAM), 2009)
This research constitutes an empirical study of influencing factors, facilitators, and inhibitors to the choice of teleworking mode in the UAE context. The research reveals that gender, marital status, nationality, residence location, and work profession are relevant, whereas educational level, Internet use, number of children, age, and years of experience are irrelevant influencing factors for the choice of teleworking mode. Furthermore, the research identifies six distinct facilitators and seven distinct inhibitors. The perceived importance of most identified facilitators and inhibitors to the choice of teleworking mode in the UAE context are found almost similar among the respondents. An exception, however, is made to the association between choice of teleworking mode and individual freedom, travel overload, cost reduction, and union resistance. The study outlines the limitations of the present research and suggests some practical implications and recommendations for managers.
Keywords: 650; teleworking; information technology; facilitators; inhibitors; UAE